Intermittent hypoxia exposure-induced heat-shock protein 70 expression increases resistance of rat heart to ischemic injury - Zhong Ning; Zhang Yi; Fang Qi-Zhi; Zhou Zhao-Nian (Acta Pharmacologica Sinica, 2016)
"AIM: To quantify the levels of HSP70 induced by different durations of intermittent (high altitude) hypoxia and to correlate them with the degree of protection of the rat heart from ischemic injury. METHODS: Reverse transcriptase polymerase chain reaction (RT-PCR) was used to detect the level of HSP70 mRNA expression in rat myocardium. Ischemia/reperfusion injury was presented as severity of arrhythmias induced by occlusion and reperfusion of the left anterior descending coronary artery of rat heart. RESULTS: The level of HSP70 mRNA expression increased progressively along with the duration of intermittent hypoxia training. It was 2.6, 3.6, and 3.8 folds after 14-, 28-, and 42-d exposures compared to that of normoxia. The tolerance of rat heart to ischemia/reperfusion injury increased with hypoxia pretreatment. Such an effect was significant after rat were exposed to a 28-d intermittent hypoxia (IH). The scores for ischemia and reperfusion inducing arrhythmia for 28- and 42-d IH were 1.2 +/- 0.5, 1.0 +/- 0.5 and 1.0 +/- 0.5, 0.9 +/- 0.5 (P < 0.01 compared with 4.0 +/- 0.7, 3.3 +/- 0.6 in normoxia rats). The overexpression of HSP70 and the increased tolerance to subsequent acute ischemia/reperfusion injury could last for 2 wk after the rats (subjected to 28 d IH) returned to normoxia. Furthermore, there was a reverse correlation between the amount of HSP70 induced and the arrhythmia occurrence (r = -0.98, -0.92 for ischemia and reperfusion induced arrhythmia, P < 0.01). CONCLUSION: These results suggest that increased resistance of rat heart to ischemia/reperfusion injury after intermittent hypoxia exposure may be related to the amount of HSP70 induced."